Top incomes in the UK: Analysis of the 2015-16 survey of personal incomes - Mike Brewer; Claudia Sámano-Robles (University of Essex, Institute for Social and Economic Research (ISER), 2019)
Using administrative tax data, we estimate top income shares for the UK through to 2015-16 (at the time of writing, the UK data held by the World Income Database stopped in 2014-15). Top income shares fell back considerably in 2009, but there is now a clear upward trend: by 2015/16, the share of income going to the top 0.1 percent was the second highest it had ever been (after 2009/10). Given Burkhauser et al. (2018a)'s findings that the main dataset used to measure income inequality in the UK does not capture the incomes of the very rich (even after a statistical correction), this suggests we should modify the story about recent inequality trends to one which recognises that, while gaps across most of the distribution might be shrinking, the very rich in the UK are continuing to pull away. We present new analysis of the characteristics of those in the top 10%, top 1%, top 0.1% and top 0.01% that accounts fully for the composite records, confirming that those with the highest incomes tend to be male, aged 45 to 64, living in London or the south-east of England, and working in "finance, insurance and real estate" or providing "professional, scientific and technical services". We estimate standard errors using the bootstrap as best we can to account for the significant over-sampling of those on top incomes.
Keywords: D63; H24; 330